2013
DOI: 10.1371/journal.pone.0064496
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Integration-Free iPS Cells from Human Adult Peripheral Blood Using BCL-XL Together with Yamanaka Factors

Abstract: The ability to efficiently generate integration-free induced pluripotent stem cells (iPSCs) from the most readily available source—peripheral blood—has the potential to expedite the advances of iPSC-based therapies. We have successfully generated integration-free iPSCs from cord blood (CB) CD34+ cells with improved oriP/EBNA1-based episomal vectors (EV) using a strong spleen focus forming virus (SFFV) long terminal repeat (LTR) promoter. Here we show that Yamanaka factors (OCT4, SOX2, MYC, and KLF4)-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 84 publications
(132 reference statements)
3
101
0
Order By: Relevance
“…The third, MBX (modified vector expressing BCL-XL), expresses BCL-XL alone. The configuration of these vectors is similar to the three vectors previously published [22]. We also made a different episomal vector, called GBX (modified vector expressing GFP and BCL-XL), expressing green fluorescent protein (GFP) and human BCL-XL, linked by a P2A self-cleavage peptide, using a piggyBac (PB)-based plasmid (provided by Dr. H. Bai) in the laboratory of Dr. Z. Wang of Johns Hopkins University.…”
Section: Improved Episomal Vectors For Reprogramming Human Blood Mncssupporting
confidence: 59%
See 2 more Smart Citations
“…The third, MBX (modified vector expressing BCL-XL), expresses BCL-XL alone. The configuration of these vectors is similar to the three vectors previously published [22]. We also made a different episomal vector, called GBX (modified vector expressing GFP and BCL-XL), expressing green fluorescent protein (GFP) and human BCL-XL, linked by a P2A self-cleavage peptide, using a piggyBac (PB)-based plasmid (provided by Dr. H. Bai) in the laboratory of Dr. Z. Wang of Johns Hopkins University.…”
Section: Improved Episomal Vectors For Reprogramming Human Blood Mncssupporting
confidence: 59%
“…First, we deleted and replaced the DNA fragment (from NruI to NheI, ∼2.7 kb) containing the hygromycin selection gene controlled by the herpes simplex virus type 1 (HSV-1) thymidine kinase (TK) promoter and polyadenylation DNA sequences and the cytomegalovirus (CMV) promoter, with a short linker restoring the NruI and NheI sites. Next, we inserted the spleen focus-forming virus (SFFV) long terminal repeat promoter/enhancer (∼400 bp), which showed better gene expression than the CMV promoter in human hematopoietic cells [20,22,24]. The DNA fragment of the SFFV promoter/enhancer was synthesized by GenScript (Piscataway, NJ, http://www.genscript.com), based on the DNA sequence of the pSFFV-neo-BCL-XL expression vector [24].…”
Section: Improved Episomal Vectors For Reprogramming Human Blood Mncsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the efficiencies of iPSC induction were different among different PEF donors. Generally, iPSC induction efficiency is determined by the percentage of the marker gene expression in cells if there is a reporter system in the donor cells, such as the Oct4 promoter driving the enhanced green fluorescent protein (EGFP) system, or determined by the numbers of stable iPSC lines derived from the donor cells (Su et al, 2013;Xue et al, 2013;Zhao et al, 2009). The number of AP-positive colonies is not considered an ideal index for the efficiency of iPSC induction, because AP-positive colonies cannot represent the full reprogramming status; it is only an early reprogramming marker .…”
Section: Continued Exogenous Gene Expression In Ipsc-scnt Embryosmentioning
confidence: 99%
“…Although the four factors used originally by Yamanaka's group (Oct4, Klf4, Sox2 and c-Myc, otherwise designated OKSM) [2,7] remain commonly used, there are intense efforts to complement the "Yamanaka factors" with other factors to increase efficiency of the repogramming process, including factors as diverse as, e.g. bcl-xl [8] and E-cadherin [9].…”
Section: Introductionmentioning
confidence: 99%